Why should state government invest in college education? An equilibrium approach for the US in 2000 - Michael P. Shields (Institute for the Study of Labor (IZA), 2008)
This paper is a preliminary look at the benefits to states in the US of subsidizing college education. The benefits studies are the external benefits of college education on the earnings of both college graduates and those who have not graduated from college. In completing a college education individuals earn more. In addition, if there are positive external benefits others will also earn more because the average level of college graduates in the state has risen. This study confirms the existence of these positive externalities for the US in 2000 in estimates using the Current Population Survey. Furthermore, these external benefits are large enough that if confirmed in more complete studies would suggest that states invest too little in college education.
urn:nbn:de:101:1-2008070253
Keywords: J2; 370; Human capital; externalities; higher education; Hochschulfinanzierung; Subvention; Bildungsinvestition; Externer Effekt; Bildungsertrag; Teilstaat; USA